Evaluasi Pakan Daun Ubi Jalar dan Daun Singkong pada Kualitas Telur Itik yang Disimpan pada Suhu 5°C - Tera Fit Rayani; Sumiati Sumiati; Arif Darmawan (Institut Pertanian Bogor, 2022)
Egg yolks contain omega-3 and omega-6 fatty acids that are easily oxidized during storage, so they must be protected. The objective of this study was to evaluate the effect of feeding containing sweet potato leaves meal (TDU) and cassava leaves meal (TDS) on the quality of duck eggs stored at 5 °C for 8 weeks. This study used a completely randomized design, 6 ´ 3 factorial design with 4 replications. Factor A was feed treatment (R0 = control feed without TDU or TDS; R1 = feed containing 0% TDU and 10% TDS; R3 = feed containing 5% TDU and 0% TDS; R4 = feed containing 5% TDU and 5% TDS; R5 = f eed containing 5% TDU and 10% TDS). Factor B was egg storage time (0, 4, and 8 weeks). A total of 144 duck eggs were used in this study. The results showed no interaction between the supplementation of TDU and TDS with the storage time on the quality of stored eggs. Supplementation of TDU or TDS or their combination significantly (p<0.05) increased the yolk score and yolk egg weight. Storage time for 4 and 8 weeks significantly (p<0.05) decreased egg weight, shell percentage, egg white percentage and weight, Haugh unit, and egg yolk score, but significantly (p<0.05) increased egg yolk percentage and weight. This study concluded that supplementing 5% sweet potato leaves meal and 10% cassava leaves meal resulted in the highest egg yolk color score. Storage time for 4 weeks can still maintain duck eggs with AA quality. Keywords: cassava leaves, duck eggs quality, storage, sweet potato leaves